Overexpression of MzASMT 1, a Gene From Malus zumi Mats, Enhances Salt Tolerance in Transgenic Tobacco - Zhuang, Weibing; Liu, Tianyu; Shu, Xiaochun; Wang, Hongxue; Wang, Zhong; Wang, Tao; Zhang, Fengjiao; Qu, Shenchun (Frontiers in Plant Science, 2020)
Melatonin, widely found in various plants as a new antioxidant, could protect plants from various biotic and/or abiotic stresses, including salt stress. MzASMT 1 (KJ123721), a gene from Malus zumi Mats, is a key enzyme required for melatonin synthesis. However, whether the overexpression of MzASMT 1 could regulate the synthesis of melatonin and improve the salt tolerance in tobacco remains unknown. In this study, the overexpression of MzASMT 1 in tobacco increased the melatonin content, and the transgenic lines owned higher salt tolerance capacity. The transgenic lines overexpressing MzASMT 1 exhibited lower degree of leaf wilting, much more fresh weight, higher plant height, longer root, higher RWC of leaves, stem and root, higher chlorophyll content and Fv/Fm, which makes transgenic lines better adapt to salt stress. The transgenic lines also had higher accumulation of proline, lower accumulation of MDA, and improved antioxidant systems, which protected plants from cell damage and oxidative stress due to excess ROS accumulation under salt treatment. The transcription of salt response genes was much more highly activated in transgenic lines than these in wildtype under salt stress. The above results contributed to the understanding of functions for MzASMT 1 in tobacco under salt stress, and provided new choice for the application of MzASMT 1 in improving plant salt tolerance.